2016
DOI: 10.1124/mol.116.103358
|View full text |Cite
|
Sign up to set email alerts
|

Use-Dependent Block of Human Cardiac Sodium Channels by GS967

Abstract: GS-458967, 6-(4-(Trifluoromethoxy)phenyl)-3-(trifluoromethyl)- [1,2,4]triazolo [4,3-a]pyridine (GS967) is a recently described, novel, sodium channel inhibitor exhibiting potent antiarrhythmic effects in various in vitro and in vivo models. The antiarrhythmic mechanism has been attributed to preferential suppression of late sodium current. However, there has been no reported systematic investigation of the effects of this compound on isolated sodium channels. Here, we examined the effects of GS967 on peak (I N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
11
25
0
Order By: Relevance
“…We and others previously reported that GS967 is a potent inhibitor of persistent sodium current, with 9‐fold greater potency than phenytoin in hippocampal pyramidal neurons from Scn2a Q54 mice . Consistent with these reports, acute application of 200 nmol·L –1 GS967 or 4 μmol·L –1 phenytoin to acutely dissociated hippocampal neurons isolated from Scn8a D/+ mice resulted in inhibition of persistent sodium current without significantly affecting peak current.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We and others previously reported that GS967 is a potent inhibitor of persistent sodium current, with 9‐fold greater potency than phenytoin in hippocampal pyramidal neurons from Scn2a Q54 mice . Consistent with these reports, acute application of 200 nmol·L –1 GS967 or 4 μmol·L –1 phenytoin to acutely dissociated hippocampal neurons isolated from Scn8a D/+ mice resulted in inhibition of persistent sodium current without significantly affecting peak current.…”
Section: Discussionsupporting
confidence: 85%
“…Symbols represent mean AE standard error of the mean because poor seizure control and frequent, prolonged generalized tonic-clonic seizures are major risk factors for SUDEP. 35 GS967 was originally developed as an antiarrhythmic compound, 22,24,32,33 and may also have a direct effect on the heart. This effect may contribute to the protection against sudden death, because Scn8a D/+ mice have hyperexcitable cardiomyocytes, and episodes of bradycardia have been observed in electrocardiograms.…”
Section: Anticonvulsant Activity Of Gs967mentioning
confidence: 99%
See 2 more Smart Citations
“…However, we recently discovered additional biophysical effects of this compound on heterologously expressed cardiac sodium channels 28 . Similarly in this study, we demonstrated significant effects of GS967 on neuronal sodium current including a potent stabilization of inactivation leading to strong use-dependent block (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%